Ventriculomegaly without elevated intracranial pressure? Normal pressure hydrocephalus as a disorder of the cerebral windkessel - Mani, Racheed; Basem, Jade; Yang, Liu; Shirdel Abdolmaleki, Nahid; Ravishankar, Anand; Fiore, Susan; Djuric, Petar; Egnor, Michael (Frontiers in Neurology, 2025)
ObjectiveNormal pressure hydrocephalus (NPH) is characterized by ventriculomegaly without elevations in intracranial pressure (ICP). One way of viewing hydrocephalus is as a disorder of the cerebral windkessel. The cerebral windkessel is the system that dampens the arterial blood pressure (ABP) pulse in the cranium, transmitting this pulse from arteries to veins via the cerebrospinal fluid (CSF) path, bypassing the microvasculature to render capillary flow smooth. When the windkessel is physiologically tuned, windkessel effectiveness (W) is given by: W=IE/R, where I represents CSF path inertance (pulse magnitude), E is CSF path elastance, and R is resistance in the CSF path. In NPH, we posit that there is a combination of arteriosclerosis (blunting the CSF pulse in the SAS- lowering I), and age-related softening of brain tissue (decreasing the elastance of subarachnoid CSF pathways- lowering E).MethodsTo model the windkessel, we utilize a tank circuit with parallel inductance and capacitance to simulate the pulsatile flow of blood and CSF as alternating current (AC), and smooth flow as direct current (DC). We model NPH as a disorder of windkessel impairment by decreasing windkessel inertance (reflecting diminished CSF pulsatility in the SAS from arteriosclerosis) and decreasing intracranial elastance (reflecting age-related brain atrophy). We simulate ventriculomegaly and shunting by lowering the resistance of this circuit.ResultsIn simulating NPH using this circuit, we found significant elevations in the amplitude and power of AC in the CSF and capillary paths when inertance and elastance were decreased. Conversely, this pulse power decreased with decreased resistance in the CSF path from ventriculomegaly and shunting.ConclusionSimulations of NPH demonstrated increased amplitude and power of AC in the CSF and capillary paths due to windkessel impairment. We posit that this pulsatility is redistributed from the SAS to the ventricular CSF path, exerting pulsatile stress on the periventricular leg and bladder fibers, which may explain NPH symptomatology. Ventriculomegaly may represent an active adaptation to improve windkessel effectiveness by decreasing CSF path resistance to mitigate decreased CSF path inertance and parenchymal elastance. Shunting provides a low resistance, accessory windkessel to obviate adaptive ventriculomegaly. This has significant implications in understanding this paradoxical condition.